Effects of an Supportive-Educative Nursing Program on Caregivers’ Caring Capabilities and Abilities to Perform Activities of Daily Living of Muslim Patients with Stroke - Prateepwattanaphan, Wineeta; Jittanoon, Piyanuch; Buapetch, Aporntip (Nursing Research and Innovation Journal, 2021)
ABSTRACT: This quasi-experimental study aimed to determine the effects of an Supportive-Educative Nursing Program (SENP) on caregivers’ capabilities in caring for Muslim patients with stroke, and on the patients’ abilities to perform activities of daily living (ADLs). The sample consisted of 64 pairs of caregivers and patients with newly diagnosed stroke. They were assigned into the experimental or control groups, with 32 pairs in each group using the simple random method. The experimental group received the eight-week SENP, developed by the researchers based on Orem’s Supportive-Educative Nursing System Theory, and the control group received usual care. The data collection instruments included the demographic data and health information of caregivers and patients form, the caregiver capabilities in caring for patient assessment form, and the Barthel ADL index for patients. Data were analyzed using descriptive statistics, paired t-test, and independent t-test. Results revealed that at posttest,the mean scores of both caregiver’s capabilities in caring for Muslim patients with stroke and abilities of the patients in ADLs in the experimental group were significantly higher than at pretest. Also, at posttest, the mean score of caregivers’ capabilities in caring for the patients and abilities of the patients in the experimental group were significantly higher than those of the control group. The findings of this study indicated that the SENP could be applied to promote caregivers’ capabilities in caring for Muslim patients with stroke at home to provide care effectively, thereby enhancing patients’ abilities to perform ADLs and prevent complications of a stroke. However, this program may need to be modified for suitable use in other contexts. Keywords: Supportive-educative nursing program, Caring capabilities, Caregivers, Abilities to perform activities of daily living, Muslim patients with stroke